Detection of highly pathogenic avian influenza in Sekong Province Lao PDR 2018—Potential for improved surveillance and management in endemic regions. Issue 1 (19th July 2020) - Annand, Edward J.; High, Holly; Wong, Frank Y. K.; Phommachanh, Phouvong; Chanthavisouk, Chintana; Happold, Jonathan; Dhingra, Madhur S.; Eagles, Debbie; Britton, Philip N.; Alders, Robyn G.
Abstract: Significant global efforts have been directed towards understanding the epidemiology of highly pathogenic avian influenza (HPAI) across poultry production systems and in wild‐bird reservoirs, yet understanding of disease dynamics in the village poultry setting remains limited. This article provides a detailed account of the first laboratory‐confirmed outbreak of HPAI in the south‐eastern provinces of Lao PDR, which occurred in a village in Sekong Province in October 2018. Perspectives from an anthropologist conducting fieldwork at the time of the outbreak, clinical and epidemiological observations by an Australian veterinarian are combined with laboratory characterization and sequencing of the virus to provide insights about disease dynamics, biosecurity, outbreak response and impediments to disease surveillance. Market‐purchased chickens were considered the likely source of the outbreak. Observations highlighted the significance of a‐lack‐of pathognomonic clinical signs and commonness of high‐mortality poultry disease with consequent importance of laboratory diagnosis. Sample submission and testing was found to be efficient, despite the village being far from the national veterinary diagnostic laboratory. Extensively raised poultry play key roles in ritual, livelihoods and nutrition of rural Lao PDR people. Unfortunately, mass mortality of chickens due to diseases such as HPAI and Newcastle disease (ND) imposes a significant burden on smallholders in Lao PDR, as in most other SE Asian countries. We observed that high mortality of chickens is perceived by locals as a new 'normal' in raising poultry; this sense of it being 'normal' is a disincentive to reporting of mortality events. Establishing effective people‐centred disease‐surveillance approaches with local benefit, improving market‐biosecurity and veterinary‐service support to control vaccine‐preventable poultry diseases could all reduce mass‐mortality event frequency, improve veterinary–producer relationships and increase the likelihood that mortality events are reported. Priority in each of these aspects should be on working with smallholders and local traders, appreciating and respecting their perspectives and local knowledge.